L'Europe: dressée sur les observations de Mrs. de l'Academie Royale des Sciences et quelques autres; sur les memoires les plus recens - L'Isle, Guillaume de, 1675-1726; Loon, H. v. (Herman van) (Chez l'Auteur sur le Quai de l'Horloge a l'Aigle de l'Or, 1700)
18th century Copper engraving handcolored with watercolor. Paper contains watermark. Outline color. Relief shown pictorially. Printed in cartouche in top left corner: "L'Europe Dressée sur les Observations de Mrs. de l'Academie Royale des Sciences et quelques autres; & sur les memoires les plus recens. Par G. De L'Isle Geographe. A Paris, Chez l'Auteur sur le Quai de l'Horloge a l'Aigle d'Or. Avec Privilege du Roy pour 20. ans 1700." Printed below title cartouche on right: "C. Simonneau au et. Fec." Printed in lower right corner in border: "H. van Loon Sculpt." Printed beneath title cartouche: "Avertissement. Comme il y á plusieurs chases sur cette Carte et sur les autres qu j'ay mises au jour qui sont differentes de ce qui se trouve sur les Cartes qui ont paru jus quicy, il est apropos d'avertir icy que ce la n'est point arrive par inadvertence, et queje rends raison de ces changemens dans ma Nouvelle Introduction a la Geographie." Printed in lower right corner is a scale comparing French leagues, French marine leagues, Spanish marine leagues, German leagues, Italian miles, English miles and Russian miles. Written in ink in top right corner: "No. 23." Depicts Europe, part of northern African and part of northwestern Asia. Includes Iceland, Norway, Sweden, Denmark, Germany, Poland, Italy, France, Spain, England, Ireland, Scotland, Turkey as "Turquie Asiatique," and part of Russia as "Moscovie Asiatique" and "Moscovie Europe." Also includes Greece, Romania, Serbia, Bosnia, Hungary, Moldavia, Bulgaria, Albania, Dalmatia and Croatia within "Turquie Europne." The title cartouche is decorated with various mythological figures, a god's head at the top, cherubim, a Roman soldier with a shield showing a gorgon's head and a Roman holding a lyre. Scale: c.a. 1:10,750,000. Guillaume de L'Isle (1675-1726) was a cartographer and the Premier Geographer to the King in France beginning in 1718. His family played a significant part in the world of French cartography in the eighteenth century. At age 9, he drew his first map and at age 27 he became a member of the Académie Royale des Sciences. He studied under Jacques Cassini, acquiring knowledge in both mathematics and astronomy. Due to his academic background and his "critical approach to the maps of his predecessors," he became known as the first "scientific cartographer" (Moreland and Bannister, 132). Among his works are "Globe, map of the world and the four continents" (1700), "Atlas de Géographie" (1700-12), "Mississippi" (1701), "Carte du Mexique et de la Floride…" (c.a. 1703), "Carte de la Louisiane et du Mississippi" (1718) and posthumously, "Atlas Nouveau" (1730 and later). Following his death, his widow took up the business with a partner, Philippe Buache (Tooley 395; Moreland and Bannister, 131-2). Source(s): Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. National Library of Australia. "L'Europe [cartographic material] / dressée sur les observations de Mrs. de l'Academie Royale d'." Accessed 3 Feb 2009. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979.